PROSPECTS FOR THE DEVELOPMENT OF BUDGET ACCOUNTING AND CONTROL IN THE CONDITIONS OF THE DIGITAL ECONOMY - A. A. Najmiddinov; M. Mamatqulov (European Science Publishing, 2024)
This article theoretically substantiates the need to develop control of the state budget execution report in the conditions of the digital economy and organize its analysis. in the context of the digital economy, the procedure for developing and maintaining control of the report on the implementation of the state budget and reflecting them in the reports is described. Also, by analyzing the current state of the state budget report, proposals and recommendations have been developed on the surface of the identification and improvement of existing problems.
Keywords: Budgetary organizations, financial statements, fixed assets, state economy, Treasury, revenue forecast indicators, public finance.